RANCANG BANGUN ALAT PENYULING MINYAK ATSIRI TIPE UAP DAN AIR (Design Construction of Essential Oil Steam and Water Distillation Type) - Vanya Aulidya; Saipul Bahri Daulay; Taufik Rizaldi (Universitas Sumatera Utara, 2019)
ABSTRACT Distillation is one of the ways to take up essential oil that contained in the plant, the example is ginger. Ginger has the high oil content with specific flavor. The postharvest processing’s purpose is to make the agricultural product have a higher economic value compared to the product without processed. The purpose of this research was to design, build, test and analyze the economic value of essential oil steam and water distillation type. The parameters observed were colour of ginger oil, effective capacity, performance and economic analysis. Based on this research, it were summarized that the colour of ginger oil wasyellow - orange, effective capacity of the equipment was 0,43 ml/hour, performance of the equipment was 68,8 % and yield was 0,1%. Economic analysis basic costs for the first to the fifth year was Rp 3.244,61/ml. Break Even Point (BEP) for the first to the fifth year was 255,82 ml/year. Net Present Value (NPV) 6,75 % wasRp 16.282.254,25 and Internal Rate of Return (IRR) this equipment was 57,65 %. Keywords:Ginger, Distillation, Machine ABSTRAK Penyulingan merupakan salah satu cara untuk mengambil minyak atsiri yang terdapat pada tumbuhan, salah satu contohnya adalah jahe. Jahe memiliki kadar minyak yang cukup tinggi dengan aroma dan rasa pedas yang khas. Proses pengolahan pascapanen bertujuan agar hasil pertanian memiliki nilai ekonomis yang lebih tinggi dibandingkan sebelum dilakukan pengolahan. Penelitian ini bertujuan untuk merancang, membuat, menguji serta menganalisis nilai ekonomis alat penyuling minyak atsiri. Parameter yang diamati yaitu warna minyak jahe, kapasitas efektif alat, kinerja alat, rendemen dan analisis ekonomi. Dari hasil penelitian diperoleh warna minyak jahe yaitu kuning - oranye, kapasitas efektif alat sebesar 0,43 ml/jam, kinerja alat sebesar 68,8 % dan rendemen sebesar 0,1 %. Analisis ekonomi dari tahun pertama sampai tahun kelima yaitu Rp 3.244,61 /ml. Nilai titik impas dari tahun pertama sampai tahun kelima yaitu 255,82 ml/tahun. Nilai net present value6,75 % adalah Rp 16.282.254,25 dan nilai internal rate of return alat ini adalah sebesar 57,65 %. Kata Kunci: Jahe, Penyulingan, Mesin